2012
DOI: 10.1159/000331312
|View full text |Cite
|
Sign up to set email alerts
|

Basophil Activation Test in Allergy: Time for an Update?

Abstract: A wide range of reported evidence in the literature has shown that the quantification of basophil activation by flow cytometry (basophil activation test, BAT) has proven to be a useful tool for the assessment of immediate-type responses to allergens mediated by IgE or other mechanisms in allergic patients. The usefulness of BAT in anaphylactic adverse reactions, late-onset allergy and immunotherapy follow-up has also been demonstrated. To date, most BAT studies reported in the literature involved the capture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 227 publications
1
37
0
5
Order By: Relevance
“…32,[34][35][36][37] Therefore, there is a great need for a reliable in vitro method to complement the routine laboratory tests for sensitization/allergy when the latter show discrepancies or are not feasible. 33 Of note, Af-specific IgE levels correlated significantly with CD203c levels (Supporting Figure E7). The BAT is a specific and 15 showed no correlation between Af colonization and sensitization, it is conceivable that these different outcomes may be related to methodological differences in defining Af sensitization, colonization and the microbiological techniques employed.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…32,[34][35][36][37] Therefore, there is a great need for a reliable in vitro method to complement the routine laboratory tests for sensitization/allergy when the latter show discrepancies or are not feasible. 33 Of note, Af-specific IgE levels correlated significantly with CD203c levels (Supporting Figure E7). The BAT is a specific and 15 showed no correlation between Af colonization and sensitization, it is conceivable that these different outcomes may be related to methodological differences in defining Af sensitization, colonization and the microbiological techniques employed.…”
Section: Discussionmentioning
confidence: 89%
“…It has been shown however, that specific IgE levels tend to change over time and have to be interpreted along with the constellation of other clinical and laboratory variables and patient history to reach a diagnosis. 32,33 SPTs are often laborious and time consuming as the full investigation may take up to 72 h to complete. Furthermore, subcutaneous injection of the antigen will induce swelling, itching and reddening at the site of injection in an allergic person and is as such a source of discomfort to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneously activated basophils were estimated on 2−2,5% (patients background sample). CCR3 as a selection marker is thought to be expressed on basophils surface in a high level [2].…”
Section: To the Editormentioning
confidence: 99%
“…cell phenotyping protocols [4,5]. Advantages of BAT in allergy diagnosis are closely related to the simple fact that this assay is a cell based investigation procedure [6] and therefore, while its major value is the ability in diagnosing either an IgE-or non IgE-mediated allergy, immunotherapy and anaphylaxis and to prevent the ethical issue associated to skin tests [1], a main concern is represented by the interpretation of activation markers in a good phenotyping FC approach [7]. The Authors reported, particularly in Table 1 of their paper, that BAT false negatives might be due mainly to the existence of non releaser subjects [1].…”
Section: To the Editormentioning
confidence: 99%
“…However, it is particularly difficult to diagnose a non releaser subject through the performance of a BAT, mainly because of the many issues related to CD63 evaluation [5,7], besides to effects caused by the differential expression of membrane FceRI/IgE complexes, circulating IgEs and relationships with FcgRs [11], downregulation and intracellular recycling of Fc receptors upon activation [12,13], doses and strength of polyclonal anti-IgEs or serum IgEs in inducing an activation response from basophils in a BAT. Non releaser subjects, unless an intracellular FC evaluation of Syk, might be misled among people performing different causes to their basophils responsiveness.…”
Section: To the Editormentioning
confidence: 99%